Heat Stress Mitigation through Seed Priming Treatment in Wheat - RAVI BHUSHAN PRASAD,; MONIKA A JOSHI,; SUDIPTA BASU,; KIRAN B GAIKWAD, (Seed Research, 2026)
Wheat is a major cereal crop of the world and one third of the world's population uses it as a staple food. Presently, heat stress is a major factor limiting wheat productivity which causes more than 30% yield loss and influences various processes including physiological, growth, developmental, yield and quality of wheat. The present study was conducted to evaluate the efficacy of various priming treatment for heat stress mitigation. The field experiment was conducted during rabi 2014-15 and 2015-16 in the field of the Division of Seed Science and Technology, ICAR - Indian Agricultural Research Institute (IARI), New Delhi, India. Eleven representative varieties from different zones were planted on three sowing dates viz.; normal sown (mid-November, S,), late sown (mid-December, S₂) and extremely late sown (early January, S₁) so as to study the comparative changes experienced in heat stress versus non-heat stress environment. Seed harvested from heat stressed environment (S) was treated with different priming treatments and based on the speed of germination, best concentrations for the respective priming treatments were identified viz.; halo priming with KH₃PO₄ (1%), osmopriming (PEG- 6000@1Mpa and plant growth regulator- GA@ 50 ppm. The study revealed significant effect of all the priming treatments in increasing the plant height and yield contributing traits. Seed quality parameters also increased significantly as a result of seed priming. Seed priming with GA, was found to be the best treatment as compared to others.